The Effect of Mentha Spicata L. Dry Powder and its Different Types Extracts on Certain Biochemical Parameters and Total Anti-oxidant Capacity - Özdemir, Ayşe; Sözbilir, Nalan Bayşu (Afyon Kocatepe Üniversitesi, 2016)
The plant Mentha spicata, or peppermint, is member of the Labiatae family, commonly used in the treatment of loss of appetite, common cold, bronchitis, sinusitis, fever, nausea and vomiting, and indigestion as a herbal agent.Although anti-oxidant effects of flavonoid containing plants have been investigated largely, studies in their interactions with enzymatic and nonenzymatic antioxidants and vitamins together with dead mentha powder are rare.The present thesis was carried out to investigate the effects of certain biochemical parameters and Mentha spicata, on antı-oxidant levels.

Mentha spicata( peppermint), Labiatae familyasına ait bir bitkidir. İştah azalması, soğuk algınlığı, bronşit, sinüzit, ateş, mide bulantısı, kusma ve hazımsızlıkta kullanılan bitkisel bir ajandır. Flavonoid içerikli bitkilerin özellikle antioksidan etkileri yıllardır araştırılıyor olmasına karşın, kuru nane tozu ile birlikte enzimatik ve nonenzimatik antioksidanlar ile vitaminler arasındaki etkileşimleri ele alan çalışmalar yok denecek kadar azdır. Bu tez, Mentha spicata’nın bazı biyokimyasal parametrelere etkilerini ve antioksidan aktivitesini araştırmak amacıyla gerçekleştirilmiştir.
Mentha Spicata L. Kuru Tozunun ve Farklı Tip Ekstrelerinin Bazı Biyokimyasal Parametreler ve Total Antioksidan Kapasite Üzerine Etkileri
Keywords: Mentha Spicata L.; β-Carotene, Vitamin C; Glutathione; Antı-Oxidant